WATU GOYANG: WISATA NEGERI KHAYANGAN (PENGEMBANGAN DESA WISATA TAPAK TILAS SULTAN AGUNG, MANGUNAN) - Tanto Lailam; Awang Darumurti; Ani Yunita (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2020)
Community service program focused on developing competitive and cultured leading of tourism village. The partner of this service is "Tapak Tilas Sultan Agung" tourism village, one of the leading tourism products is Watu Goyang. This service was carried out with active participation through training, assistance, and development facilitation. Some of the programs that have carried out are: (1) strengthening human resources by organizing of tourism village, training includes: financial coaching, marketing training, innovation tourism product, package marketing training, marketing communication, and digital marketing training; (2) Outbound tourism, this development have carried out by providing training of trainers, and packaging outbound in watu goyang; (3) Packaging tourism products by applying the concept of "living in" in a tourist village, (4) Facilitating the development of watu goyang, carried out with various things: provider of superior tourist product information boards and information on watu goyang tourism map; (5) making the watu goyang tourism map; (6) changes in the new brand of watu goyang "watu goyang: wisata negeri khayangan" and carried out various promotions through websites, social media, and others.